PENGARUH KINERJA GURU PAI TERHADAP MINAT BELAJAR SISWA - Eva Selvia (Universitas Djuanda, 2015)
Interest is a very important thing for the students in the learning process. Students who have an interest in him to learn, then the student can easily absorb the lessons he had learned. On the contrary, in the absence of interest and attention within a student's response to what he had learned, students will not be able to master the subject matter which he had learned it well. Therefore, interest in studying students is very noteworthy and enhanced by teachers as educators at the school. To generate interest, students learning the many ways that can be used, one of them the performance of teachers in may teach. The performance is a manifestation of a person's behaviour with the orientation of achievement. The performance of the teacher in the learning process of how a teacher to plan learning activities learning, implementing, and assessing learning outcomes. This research is quantitative types of research. The withdrawal of the sample size using a simple random sampling method, and the collection of data in this study is the question form, interview, observation and documentation. As for the data analysis techniques using simple regression. Finallay, the results prove that there is a positive and significant influence from Islamic teacher performance against learning interest of students in public high schools 1 Caringin Bogor, so the better the Islamic teacher performance then learning interest of students will be getting better.